If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 3y = 180 Solving 12x + 3y = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 12x + 3y + -3y = 180 + -3y Combine like terms: 3y + -3y = 0 12x + 0 = 180 + -3y 12x = 180 + -3y Divide each side by '12'. x = 15 + -0.25y Simplifying x = 15 + -0.25y
| -5x-68=4x+40 | | 123x+56=6 | | -6x-69=35+2x | | 2+y=0 | | 9x-19=6x+47 | | (b+9)(b-6)=0 | | -9x-40=3x+32 | | 6x-69=-3x+30 | | x^2+31x+43= | | Y=60+5x | | 3x^2-24x-60=0 | | 6-x+4=19 | | x^2+12x=-25 | | x^4+7x^3+8x^2-7x+15=0 | | 12c^2+19x-21=0 | | 12x^2+25-7=0 | | 10n=109 | | 12*-1=y | | (x+6)(x+6)-11=0 | | 12-20y=20 | | (y-1)(y-1)=16 | | 3(p-1)=4(2p+7) | | 5(5+x)=3(x+7) | | 8+5x+6(10x)=608+5x | | 2x=52 | | 8y^2+22y-21= | | 2*x^2-2x-66=7 | | u^2=98 | | 2*x-66=7 | | 11x^2+7x=0 | | 3+5=z | | 67=(x)(.5x) |